2011
DOI: 10.1111/j.1540-5907.2011.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment, Regime Type, and Labor Protest in Developing Countries

Abstract: We explore the relationship between FDI, regime type, and strikes in low-and middle-income countries. We argue that FDI produces social tensions and opportunities for protest that can result in higher levels of industrial conflict. However, the effect of FDI is moderated by regime type. While democracies tend to have higher levels of protest overall, they are better able than authoritarian regimes to cope with the strains arising from FDI. We cite two reasons. First, political competition forces regimes to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 37 publications
2
40
0
1
Order By: Relevance
“…In authoritarian periods, workers lack both allies and the capacity to disrupt production. Strikes succeed when workers halt production or when government and business are dependent on foreign capital (Seidman 1994;Robertson and Teitelbaum 2011). Workers' success reflects their structural and associational power.…”
Section: Explaining Strike Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In authoritarian periods, workers lack both allies and the capacity to disrupt production. Strikes succeed when workers halt production or when government and business are dependent on foreign capital (Seidman 1994;Robertson and Teitelbaum 2011). Workers' success reflects their structural and associational power.…”
Section: Explaining Strike Outcomesmentioning
confidence: 99%
“…Furthermore, international businesses might have been reluctant to invest in MADECO if management or the government repressed the union, as supporting government repression could stain their reputation and encourage protests in the United States (see Robertson and Teitelbaum 2011). Therefore, even though the union faced management repression and had no congressional allies, the strikers' mobilization at the factory gates, as well as the dependence of the government and the company on international capital, allowed the union to successfully mobilize at the local, national, and international scales and claim victory.…”
Section: The 1993 Strikementioning
confidence: 99%
“…Moreover, democratic regimes seem to do a better job at institutionalizing labor grievances. 10 China, like other authoritarian regimes, has dif½culty committing to the institutionalization of social conflict because it heightens the possibility of social empowerment. The state remains in charge, which also means that labor-capital conflict almost invariably metastasizes into a confrontation between workers and the state.…”
mentioning
confidence: 99%
“…As political scientists Graeme Robertson and Emmanuel Teitelbaum have found, democratic regimes often do better in insulating labor conflict via institutional channels. 44 Other researchers have found that democratization tames labor by enveloping unions and activists into party politics and their crosscutting cleavages. Authoritarian regimes, fearful of the potential externalities of autonomous labor, seem to prefer ad hoc and reactive responses to spontaneous forms of worker action, such as wildcat strikes, traf½c blockades, and episodic violence.…”
mentioning
confidence: 99%
“…For example, Robertson and Teitelbaum (2011) show that FDI leads to increases in labor protests, especially when the host economy has inadequate labor rights protections. Our sub national study similarly nds that the combination of outside capital and de cient protection of land rights can generate serious predation of farmers' land.…”
Section: Discussionmentioning
confidence: 99%